Utilizing Biomass-Based Graphene Oxide–Polyaniline–Ag Electrodes in Microbial Fuel Cells to Boost Energy Generation and Heavy Metal Removal - Asim Ali, Yaqoob; Albert, Serra; Showkat, Ahmad Bhawani; Mohamad Nasir, Mohamad Ibrahim; Anish, Khan; Alorfi, Hajer S.; Abdullah, M. Asiri; Mahmoud, Ali Hussein; Imran, Khan; Khalid, Umar (MDPI, 2022)
Although regarded as environmentally stable, bioelectrochemical fuel cells or, microbial fuel cells (MFCs) continue to face challenges with sustaining electron transport. In response, we examined the performance of two graphene composite-based anode electrodes—graphene oxide (GO) and GO–polymer–metal oxide (GO–PANI–Ag)—prepared from biomass and used in MFCs. Over 7 days of operation, GO energy efficiency peaked at 1.022 mW/m2 and GO–PANI–Ag at 2.09 mW/m2 . We also tested how well the MFCs could remove heavy metal ions from synthetic wastewater, a secondary application of MFCs that offers considerable benefits. Overall, GO–PANI–Ag had a higher removal rate than GO, with 78.10% removal of Pb(II) and 80.25% removal of Cd(II). Material characterizations, electrochemical testing, and microbial testing conducted to validate the anodes performance confirmed that using new materials as electrodes in MFCs can be an attractive approach to improve the electron transportation. When used with a natural organic substrate (e.g., sugar cane juice), they also present fewer challenges. We also optimized different parameters to confirm the efficiency of the MFCs under various operating conditions. Considering those results, we discuss some lingering challenges and potential possibilities for MFCs